Commensal Bacteria Impact on Intestinal Toll-like Receptor Signaling in Salmonella-Challenged Gnotobiotic Piglets - Splichalova, Alla; Kindlova, Zdislava; Killer, Jiri; Neuzil Bunesova, Vera; Vlkova, Eva; Valaskova, Barbora; Pechar, Radko; Polakova, Katerina; Splichal, Igor (Pathogens (Basel, Switzerland), 2023)
Gnotobiotic (GN) animals with simple and defined microbiota can help to elucidate host-pathogen interferences. Hysterectomy-derived germ-free (GF) minipigs were associated at 4 and 24 h post-hysterectomy with porcine commensal mucinolytic Bifidobacterium boum RP36 (RP36) strain or non-mucinolytic strain RP37 (RP37) or at 4 h post-hysterectomy with Lactobacillus amylovorus (LA). One-week-old GN minipigs were infected with Salmonella Typhimurium LT2 strain (LT2). We monitored histological changes in the ileum, mRNA expression of Toll-like receptors (TLRs) 2, 4, and 9 and their related molecules lipopolysaccharide-binding protein (LBP), coreceptors MD-2 and CD14, adaptor proteins MyD88 and TRIF, and receptor for advanced glycation end products (RAGE) in the ileum and colon. LT2 significantly induced expression of TLR2, TLR4, MyD88, LBP, MD-2, and CD14 in the ileum and TLR4, MyD88, TRIF, LBP, and CD14 in the colon. The LT2 infection also significantly increased plasmatic levels of inflammatory markers interleukin (IL)-6 and IL-12/23p40. The previous colonization with RP37 alleviated damage of the ileum caused by the Salmonella infection, and RP37 and LA downregulated plasmatic levels of IL-6. A defined oligo-microbiota composed of bacterial species with selected properties should probably be more effective in downregulating inflammatory response than single bacteria.
Keywords: Bifidobacterium; Lactobacillus; cytokines; Salmonella Typhimurium; Toll-like receptor; gnotobiotic minipig; lipopolysaccharide